The state of the Italian Republic. Issue 2 (3rd April 2019) - Pasquino, Gianfranco
ABSTRACT: There have traditionally been several obstacles in the way of the smooth functioning of the Italian political system. This article explores recent changes in the government, Parliament, the political parties, the party system and the Presidency in order to evaluate the state of the Republic. The undermining of the role of Parliament and the assertion of presidential powers are the two most significant new phenomena. The weakest link is found in the decline and the degeneration of the parties and the deconstruction of the party system. Poorly organised, personal, parties lacking any political culture are negatively affecting the quality of Italian democracy.